Optimization of solvent extraction conditions of Cambodian soybean oil using response surface methodology - Mich, Monika; Kong, Sela; Say, Manit; Nat, Yukleav; Tan, Chin Ping; Tan, Reasmey (Journal of Food Technology Research, 2023)
The conventional solvent extraction (CSE) method is commonly used to extract oil from oilseeds. Even though the extraction of oil from soybean seeds using the CSE method has been studied extensively, the application of response surface methodology (RSM) has not yet been widely explored. In this paper, the CSE method was employed using three different types of solvents – ethanol (Eth), n-hexane (Hex), and a mixture of Hex:Eth in a ratio of 2:1 – and optimized using RSM to extract the oil from Cambodian soybean seeds. For each solvent, a central composite design (CCD) was applied to optimize the extraction conditions, such as the extraction times (15, 30, and 45 min) and solvent-to-solid ratios (5:1, 10:1, and 15:1 mL/g). This CCD generated 11 experimental runs for each type of solvent. The optimum oil yields when using ethanol, Hex:Eth, and n-hexane were 20.53%, 18.78%, and 17.39%, respectively. The optimum condition was obtained at 15 min extraction time and 15:1 (mL/g) solvent-to-solid ratio for all solvent types. The coefficients of determination of ethanol, Hex:Eth, and n-hexane were 0.9710, 0.9954, and 0.9263, respectively, which mathematically indicated a good model for the prediction. Therefore, the model was considered accurate and reliable for predicting oil yields in this study.